The Scout Movement and Indonesian National Identity: A Critical Reflection - Haflah Leste Distincta (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2025)
The development of the Scout Movement in Indonesia, which originated from the early scouting movement, cannot be separated from the government policies during the Soekarno era—namely the Political Manifesto, the 1945 Constitution, Indonesian Socialism, Guided Democracy, and the Indonesian Personality—collectively known as Manipol Usdek. This was Soekarno’s grand vision of creating a just and prosperous Indonesia rooted in the noble values of Pancasila. The scouting movement has long contributed to strengthening Indonesia’s national identity and promoting national integration. Therefore, contemporary government policies should ideally support the institutionalization of nationalism through today’s Scout Movement. This study employs a qualitative approach using a literature review method.